2022
DOI: 10.1093/hmg/ddac284
|View full text |Cite
|
Sign up to set email alerts
|

A functional variant ofCD40modulates clearance of hepatitis B virus in hepatocytes via regulation of the ANXA2/CD40/BST2 axis

Abstract: More than 250 million people in the world are chronically infected with hepatitis B virus (HBV), which causes serious complications. Host genetic susceptibility is essential for CHB, and our previous genome-wide association study identified a single-nucleotide polymorphism (SNP), rs1883832, in the 5′ untranslated region of CD40 predisposing to chronic HBV infection, but the underlying mechanism remains undefined. This study aimed to investigate whether rs1883832 was the real functional SNP (fSNP) of CD40 and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…One possibility is that BST2 exerts anti‐HBV activity partly due to its blocking of intracellular virus budding. Moreover, we previously demonstrated that BST2 was regulated by the JAK–STAT pathway 22 . Other studies indicated that boosting the expression of methylated STAT1 and S‐adenosyl methionine might elevate IFNα's antiviral impact 34 .…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…One possibility is that BST2 exerts anti‐HBV activity partly due to its blocking of intracellular virus budding. Moreover, we previously demonstrated that BST2 was regulated by the JAK–STAT pathway 22 . Other studies indicated that boosting the expression of methylated STAT1 and S‐adenosyl methionine might elevate IFNα's antiviral impact 34 .…”
Section: Discussionmentioning
confidence: 96%
“…We have previously identified that BST2 exerts an inhibitory effect on HBV. 22 It has been reported that BST2 is recognized as an IFN-stimulated gene (ISG), 23 indicating it may inhibit HBV replication due to being highly inducible by IFN in human hepatoma cells. Thus, we investigated whether IFN stimulation might alter BST2 expression.…”
Section: Ifn Induces Bst2 Expressionmentioning
confidence: 99%
See 3 more Smart Citations